Epidydimal leiomyosarcoma: a rare case of scrotal swelling - Krishnan, Sharath K.; Chirukandath, Ravindran; Kunhikandilakath, Safna; Vava, Harikumar Kaniyamparambil; John, Babu Pulluvelil (International Surgery Journal, 2020)
Sarcomas of the genitourinary tract are extremely uncommon and accounts for only 1-2% of genito urinary malignancies. Sarcomas of the para testicular region, comprising tissues such as the epididymis, spermatic cord, inguinal canal and testicular tunica are also extremely rare. epidydimal leiomyosarcoma accounted only for 4 percentage of all para testicular tumours and only 16 cases are reported so far in literature and they account 4% of all Para testicular sarcomas. We are presenting a 61-year-old patient presented with a hard welling of 1 year duration, with no other associated symptoms. On ultrasound evaluation, it was reported as extra testicular lesion, possibly from epididymal tail. We performed a high inguinal orchidectomy. Histopathological examination revealed a para testicular leiomyosarcoma arising from epididymis. This case has discussed because of the rarity of the disease and possible cure if diagnosed early and treated aggressively.